Development of Performance Assessment Tools for Supervision Consultants in Infrastructure Projects - Rarasati, Ayomi Dita; Wahyu Putra Rahman (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
The construction of toll roads requires supervision consultants capable of ensuring project quality, time, and cost performance, yet a structured and measurable assessment framework is lacking. This study develops a comprehensive performance assessment rubric for toll road supervision consultants using quantitative methods, including a literature review, a survey of 50 respondents, validation by six experts, and an application test by 12 evaluators. Data were analyzed using validity and reliability tests, Mann–Whitney U, AHP, TOPSIS, and ROC methods. The results identified 18 valid and reliable indicators grouped into three dimensions soft skills, technical skills, and project supervision. The most critical indicators were QA/QC (C=0.810), periodic reporting (0.782), and work volume management (0.711). Final dimension weights were 40% for technical skills, 30% for soft skills, and 30% for project supervision. Application of the rubric indicated consultants’ performance remained in the “Average” category, highlighting areas for measurable improvement in supervision practice.